Methods to Assess Adult and Adolescent Patients’ Adherence to Antimalarial Treatment: A Systematic Review - Santos, Heloísa Ferreira Pinto; Guaraldo, Lusiele; Pedro, Renata Saraiva; Damasceno, Luana Santana; Daniel-Ribeiro, Cláudio Tadeu; Brasil, Patrícia (Frontiers in Pharmacology, 2022)
Malaria is a curable disease for which early diagnosis and treatment, together with the elimination of vectors, are the principal control tools. Non-adherence to antimalarial treatment may contribute to therapeutic failure, development of antimalarial resistance, introduction or resurgence of malaria in non-endemic areas, and increased healthcare costs. The literature describes several methods to directly or indirectly assess adherence to treatment, but no gold standard exists. The main purpose of this review is to systematize the methods used to assess patient adherence to antimalarial treatment. A systematic review was performed, in accordance with the PRISMA statement, of the following databases: LILACS, EMBASE, PUBMED, COCHRANE, GOOGLE SCHOLAR, WEB OF SCIENCE, SCOPUS, and OPENGREY, through 14 December 2021. A snowball search was also performed by screening the references of the included studies as well as those cited in relevant reviews. Inclusion criteria were reporting assessment of the patient’s adherence to antimalarials in individuals with laboratory diagnosis of malaria, the description of antimalarials prescribed, and adherence estimates. Exclusion criteria were studies exclusively about directly observed therapy, studies of populations ≤12 yo and guidelines, commentaries, reviews, letters, or editorials. Study quality was assessed using MINORS and the Cochrane Risk of Bias Tool. Proportions were calculated to measure frequencies considering the number of articles as the denominator. Twenty-one studies were included in this review. Most of them (76.5%) assessed adherence to falciparum malaria treatment. Seventeen studies (80.9%) used a combination of methods. The methods described were pill counts, self-reports, biological assays, use of electronic pillboxes, and clinical cure. It was possible to identify different adherence classifications for all the methods used. Our review found that indirect methods like pill counts and self-reports are the most commonly used. Combining an method that gives solid proof of the ingestion of medication and a method that completes the research with information regarding factors, beliefs or barrier of adherence seems to be the best approach. Future studies of antimalarial treatment should standardize adherence classifications, and collect data on the types and causes of nonadherence, which can contribute to the development of tools to promote medication adherence. Prospero registration number: CRD42020148054.